2014
DOI: 10.1080/17290376.2014.985700
|View full text |Cite
|
Sign up to set email alerts
|

Health behaviour change of people living with HIV after a comprehensive community-based HIV stigma reduction intervention in North-West Province in South Africa

Abstract: All over the world, health behaviour is considered a complex, far reaching and powerful phenomenon. People's lives are influenced by their own or others' health behaviour on a daily basis. Whether it has to do with smoking, drinking, pollution, global warming or HIV management, it touches lives and it challenges personal and community responses. Health behaviour, and health behaviour change, probably holds the key to many a person's immediate or prolonged life or death outcomes. The same can be said about comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Hartog et al (Tshabalala and Visser, 2011;Nyamathi et al, 2013;Sermrittirong et al, 2014;Go et al, 2017;Li et al, 2018) IC-CBT Cognitive Behaviour Therapy: a structured approach in which patients are trained to identify and modify negative beliefs and negative interpretations (Lusli et al, 2016) b and (Tshabalala and Visser, 2011;Li et al, 2018) Empowerment Empowerment -Contact Facilitated contact between stigmatised, learning from other stigmatised persons Nambiar et al (2011) Empowerment -Education Information for persons from the stigmatised population to understand their condition and to improve it, such as proper nutrition, responsible disclosure management (Elafros et al, 2013;Chidrawi et al, 2014) b and (Cornish, 2006;Nambiar et al, 2011;Nyamathi et al, 2013;Doosti-Irani et al, 2017;Lyons et al, 2017;Shamsaei et al, 2018) Empowerment - Group counselling Sharing, discussing with a group about topic as shared experience, positive identity change, internal stigma, disclosure and coping (Dalen, 2009;Lusli et al, 2016)b and (Koen et al, 2010;…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hartog et al (Tshabalala and Visser, 2011;Nyamathi et al, 2013;Sermrittirong et al, 2014;Go et al, 2017;Li et al, 2018) IC-CBT Cognitive Behaviour Therapy: a structured approach in which patients are trained to identify and modify negative beliefs and negative interpretations (Lusli et al, 2016) b and (Tshabalala and Visser, 2011;Li et al, 2018) Empowerment Empowerment -Contact Facilitated contact between stigmatised, learning from other stigmatised persons Nambiar et al (2011) Empowerment -Education Information for persons from the stigmatised population to understand their condition and to improve it, such as proper nutrition, responsible disclosure management (Elafros et al, 2013;Chidrawi et al, 2014) b and (Cornish, 2006;Nambiar et al, 2011;Nyamathi et al, 2013;Doosti-Irani et al, 2017;Lyons et al, 2017;Shamsaei et al, 2018) Empowerment - Group counselling Sharing, discussing with a group about topic as shared experience, positive identity change, internal stigma, disclosure and coping (Dalen, 2009;Lusli et al, 2016)b and (Koen et al, 2010;…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…In the community going door to door, organising a community walk or awareness raising workshops, community mobilisation (Dalen, 2009;Jain et al, 2013) b and (Boulay et al, 2008;Doosti-Irani et al, 2017;Go et al, 2017;Maulik et al, 2017) Education -Popular Opinion Leaders Local leaders, such as religious leaders, proactively speak out to improve the situation of the stigmatised population through churches or in other places within the community (Apinundecha et al, 2007;Boulay et al, 2008) Contact Contact -Direct Short-term contact between the general population and representation from the stigmatised population to share information and ask questions (Jain et al, 2013) b and (Raju et al, 2008;Jain et al, 2013;Chidrawi et al, 2014;Peters et al, 2015;Prinsloo and Greeff, 2016;Ahuja et al, 2017;Dadun et al, 2017;Doosti-Irani et al, 2017) Contact -Direct Cooperation Interaction or collaboration between the general population and the stigmatised population is facilitated (Chidrawi et al, 2014) b and (Apinundecha et al, 2007;Raju et al, 2008;…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Previous studies have indicated that health behavior and health behavior change are some of the complex phenomena in behavioral sciences 40,41. This study aimed to investigate whether self-efficacy could mediate the effect of individual beliefs (perceived severity, susceptibility, benefits and barriers) about their health behavior in relation to NCD prevention and management intervention at the community level.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma reduction has been documented to improve the quality of life and patient outcomes. A study in South Africa found stigma reduction for PLHIV resulted in a shift in self-judgement that led to behavior change, including fewer symptoms, improved treatment adherence, and improved relationships and quality of life [ 26 ].…”
Section: Discussionmentioning
confidence: 99%